PERAN TATA USAHA DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN SEKOLAH DI SMK SWASTA MANDIRI - Syifa, Salsabila Mayla Nadhira; Siahaan, Amiruddin (STKIP Pesisir Selatan, 2026)
This study aims to analyze the role of administrative staff in improving the effectiveness of school management at SMK Swasta Mandiri. Administrative staff constitute a strategic element within the school’s organizational structure, functioning to manage administration, provide data, and support the principal’s decision-making process. Qualitative descriptive research was used in this study whereby observations, interviews, and documentation were used to compile data. The study's subjects included the school principal, head of administration, administrative staff members, and teachers. The findings indicate that administrative staff make a significant contribution to the effectiveness of school management through orderly administrative management, accurate data provision, and responsive administrative services. However, several challenges remain, including limited digital competencies, partially manual administrative systems, and suboptimal coordination between the principal and the administrative unit. Strategies to enhance professionalism through training programs, administrative digitalization, performance evaluation, and strengthened internal communication are essential solutions to improve school management effectiveness. Therefore, administrative staff do not merely function as administrative executors but also serve as strategic partners in realizing effective, efficient, and professional school governance.